Jonadab son of Shimeah: A Figure Wrapped in Controversy - Keren, Orly; Taragan, Hagit (Old Testament Essays, 2022)
Jonadab son of Shimeah was King David’s nephew. His character can be evaluated on the basis of the two brief scenes where he appeared in 2 Sam 13:3–5, 30–37. The article surveys four aspects of the controversy that swirls around Jonadab’s moral nature: The terms used to describe him, namely, “friend” and “a very smart man,” which can be interpreted as “wise in evil counsel” (b. Sanh. 21a) or as “intelligent and perspicacious”; The assessment of his conduct and relations with the other characters—Amnon, Tamar, Absalom, and David; How he fits into the narrative as a whole and whether he is a main or supporting character; How the editor revised the original author’s text of this chapter. The first three aspects allow an examination of Jonadab’s moral character, the fourth determining whether his presence is essential to the story. https://doi.org/10.17159/2312-3621/2021/v34n3a4